Cracking the case of circadian rhythms by Drosophila genetics - Hall, Jeffrey C. (Henry Stewart Talks, 2008)
Rhythm mutants, Identification of the corresponding genes and inferences about their products, Manipulation of such genes amd product functions to elucidate not only the neural substrates of behavioral rhythmicities, but also the intracellular mechanisms that comprise biological clocks, Identification of additional rhythm-related genes in their normal forms, followed by analogous manipulations of them, Analyses of core clock functions in context of rhythm-related processes that surround such central "pacemaking", that is: environmental inputs to the clock and how its actions are output to regulate revealed rhythms
Reviewed at 2018/05/31